(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Man The objective of this article is to examine the relationship, causal and quality factors of financial reports and financial success of Thai small hotel businesses. This was a qualitative research using in-depth interviews. To find out the relationship patterns that affect the quality of financial reports and financial success. The research area was hotel business in 12 cities. The sample group was accounting and finance executives. The hotel business owner and the specific method using in-depth interview form for data analysis. The research found that professional accounting skills were associated with the quality of financial reporting and the financial success of the hotel business. And the ethics of the accounting profession relate to the quality of financial reports and the financial success of the hotel business. The management of the accounting department is concerned with the quality of the financial reports and the financial success of the hotel business. The quality of financial reports is related to the financial success of the hotel business. The financial success of the hotel business is profit, revenue, cost, indicators of cost success should take into account the use of resources. The cost of the time reduced and the cost of the investment to be recovered in comparison with the results.